2022
DOI: 10.3390/nu14194098
|View full text |Cite
|
Sign up to set email alerts
|

Who Likes Unhealthy Food with a Strong Flavour? Influence of Sex, Age, Body Mass Index, Smoking and Olfactory Efficiency on Junk Food Preferences

Abstract: Background. Unhealthy food is an important element in the development of diseases of civilisation. The aim of this study was to determine how sex, age, body mass index, smoking and olfactory efficiency influence the consumption of such foods. Methods. A total of 283 people living in the Silesian Voivodeship in Poland took part in the study. They were aged 18–82. An interview and olfactory tests were conducted together with assessments of food preferences from 25 types of food products. The extent to which sex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…There are significant sex differences in humans' consumption of palatable foods. Women rate low-calorie food images higher (Legget et al, 2023) and report liking unhealthy foods less than men [ 58 ]. Images of food increase activation of the lateral dorsolateral prefrontal cortex in women more than in men [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are significant sex differences in humans' consumption of palatable foods. Women rate low-calorie food images higher (Legget et al, 2023) and report liking unhealthy foods less than men [ 58 ]. Images of food increase activation of the lateral dorsolateral prefrontal cortex in women more than in men [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zia (2017), reported that females (aged 20–40 years) prioritize taste and flavor in deciding to purchase packaged food. Another recent study reported young adults had a greater preference to unhealthy packaged food with strong flavors (Hartman-Petrycka et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The current food preferences of adolescents tend unhealthy foods and drinks that contain high sugar, fat, and calories, as well as low nutritional value for the body. High frequent of low-nutrient foods can contribute to health problems such as overnutrition 14 .…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…Food preferences refer to the level of liking or disliking specific foods. Adolescents tend to prefer unhealthy, high-calorie, and low-nutrient foods, such as sweet and fatty foods, which can contribute to health problems 14 . Studies show that food preferences are related to the occurrence of obesity 15 . Adolescents with nutritional excess tend to prefer fatty and sweet foods 16 .…”
Section: Introductionmentioning
confidence: 99%